Nursing considerations: future of stem cell transplantation in Egypt - Mohammed Mohammed, Hanan; El-Said Hassane, Abeer (International Journal of Nursing Research, 2023)
Background: The procedure of hematopoietic stem cell transplantation (HSCT) will keep expanding over the next decades. All around the world, although enormous technological advancement and improvement of scientific approaches to fighting all diseases; especially blood diseases as white blood cell (WBC) disorders, the people still sick and they need treatment. In Egypt, stem cells offer exciting promise for future therapies, but significant technical hurdles remain that will only be overcome through years of intensive research. Since hematopoietic stem cell transplantation started, nurses play an important role in this procedure, qualified nurses involved in every step of the stem cell collection process. They prepared with the knowledge and practice about the cord blood gathering and stem cell banking procedure to do; otherwise, nurses acting an accurate group of functions in stem cell banking, from their understanding the structure of the umbilical cord to defining the sites of obtaining stem cells. Specialized nursing care is essential to avoid and manage the predicted and unpredicted complications of hematopoietic stem cell transplantation. Stem cell transplantation needs to the highly qualified nursing team, their care continuing within phases of transplant for both donors and patients. This article will describe the future of stem cell transplantation in Egypt and Arab world, the most important issues and trends related to HSCT, the Benefits of Umbilical Cord Blood Stem Cell Storage in Stem Cell Banking the formal unities and hospitals for HSCT in Egypt and the nurses’ role in stem cells transplantation (Pre, During, Post and Discharge) in Egypt.